Risk factors and their negative impact on the formation reproductive function (Overview) (Eurasian Scientific Herald, 2022)
The identification of risk factors and the prediction of disorders of the reproductive health of adolescent girls, the development of a modern strategy for the formation of reproductive potential by strengthening the preventive focus is an actual practical area of national health care.